2014
DOI: 10.1167/iovs.13-13724
|View full text |Cite
|
Sign up to set email alerts
|

Cone Photoreceptors Develop Normally in the Absence of Functional Rod Photoreceptors in a Transgenic Swine Model of Retinitis Pigmentosa

Abstract: Lack of early scotopic function in TgP23H swine suggests it as a model of an aggressive form of RP. In this mammalian model of RP, normal cone function develops independent of rod function. Therefore, its retina represents a system in which therapies to rescue cones can be developed to prolong photopic visual function in RP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 43 publications
0
33
1
Order By: Relevance
“…Our results support the hypothesis that one of the roles of curcumin neuroprotection is to prevent mistrafficking of mutant rhodopsin protein that results in abnormal expression throughout the rod PR. In our previous studies 28,30 we showed that abnormal expression of mutant rhodopsin in P23H miniswine embryos is associated with malformation of rod PR outer segments and spherules, and that P23H piglets never develop rod-driven vision. The amelioration of the morphologic abnormality with curcumin treatment is an important first step because normal rod PRs are a prerequisite to their normal function.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Our results support the hypothesis that one of the roles of curcumin neuroprotection is to prevent mistrafficking of mutant rhodopsin protein that results in abnormal expression throughout the rod PR. In our previous studies 28,30 we showed that abnormal expression of mutant rhodopsin in P23H miniswine embryos is associated with malformation of rod PR outer segments and spherules, and that P23H piglets never develop rod-driven vision. The amelioration of the morphologic abnormality with curcumin treatment is an important first step because normal rod PRs are a prerequisite to their normal function.…”
Section: Discussionmentioning
confidence: 87%
“…In the Tg P23H rat, where the onset of photoreceptor degeneration is significantly later compared with the Tg pig. 28,30 In addition to curcumin 17 other compounds that produce positive results include: safranal, 36 cannabinoid agonist HU210, 37 tauroursodeoxycholic acid (TUD-CA) 38 proinsulin, 39 Tat-lCL (specific peptide inhibitor of mitochondrial l-calpain), 40 and arimoclomol (heat-shock response coinducer). 41 Neither our study nor the work in the rat have explored the long-term effects of these factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blocks of corneal tissue were cut into 4μm-thick sections using a Leica EMUC6 Ultramicrotome (Leica Microsystems, Buffalo Grove, IL), stained with 1% cresyl violet (Sigma, St. Louis, MO), mounted, and cover-slipped. For TEM, sections were prepared as previously described (Fernandez de Castro et al, 2014; Scott et al ., 2014) and examined with a transmission electron microscope (TEM; Model 300: Phillips, Eindhoven, The Netherlands). Photomicrographs were captured with a digital camera (15 M pixel digital camera, Scientific Instruments and Applications, Duluth, GA) and Maxim DL Version 5 software (Diffraction Limited, Ottawa, Canada).…”
Section: Methodsmentioning
confidence: 99%